Case report: Disseminated intravascular coagulation in a dog following treatment with melarsomine for Dirofilaria immitis - Philp, Helen S.; Farrell, Kate S.; Li, Ronald H. L. (Frontiers in Veterinary Science, 2023)
Disseminated intravascular coagulation following melarsomine therapy for Dirofilaria immitis (D. immitis) is reported in a 9-year-old female intact pit bull-type dog. The dog had been diagnosed with D. immitis (antigen and microfilaria positive) and treated with imidacloprid, moxidectin, doxycycline and 3 doses of melarsomine over a 92-day period. Seven days after the third melarsomine injection, the patient was presented to her family veterinarian due to right pelvic limb swelling. Prothrombin and activated partial thromboplastin times were prolonged beyond the detectable range. Treatment included vitamin K1 and fresh frozen plasma (FFP) prior to referral to the authors’ institution. At this time the patient remained coagulopathic. Further investigations included thoracic radiographs, abdominal ultrasound and an echocardiogram. The patient was administered multiple units of packed red blood cells and FFP, sildenafil, dexamethasone SP, aminocaproic acid and vitamin K1. Repeat CBC approximately 20 hours after admission showed persistent anemia and thrombocytopenia. Despite ongoing administration of FFP, a repeat coagulation panel showed worsening of the coagulopathy with prothrombin time of 84.2s (reference interval (RI) 7.0-9.3s), activated partial thromboplastin time > 140s (RI 10.4-12.9s) and fibrinogen < 50mg/dL (RI 109-311mg/dL). Following discussion with the owners, the patient was euthanized. Necropsy was performed and confirmed heartworm infection with severe pulmonary arterial thrombosis, vascular remodeling, and intraluminal degenerate nematodes. Multifocal subcutaneous and organ hemorrhage was apparent. Although coagulopathy has been described in caval syndrome associated with heartworm disease and is listed as a potential side effect of melarsomine administration, this is the first report of documented disseminated intravascular coagulation following melarsomine treatment for D. immitis. Potential mechanisms for the coagulopathy are discussed and the case report highlights a rare, but serious complication of adulticide therapy.